Exploring Strobilanthes crispus as a Sustainable Corrosion Inhibitor for Aluminium: Electrochemical Insight Across pH Variations - Albarqouni, Yasin; Binti Wan Md Zain, Wan Salwanis; Agi, Augustine; Bin Abdullah, Arman (Indonesian Journal of Chemistry, 2026)
Strobilanthes crispus leaf extract was investigated as a green corrosion inhibitor for aluminium in varying pH media (HCl pH 2, NaCl pH 7, NaOH pH 10). FTIR confirmed C–O and C=O functional groups are critical for inhibition. Weight loss measurements after 20 d in NaOH showed corrosion rates of 0.00061 mm/y at 0.2 mg/L inhibitor and 0.00038 mm/y at 0.8 mg/L, with efficiencies of 46.8 and 67.05%, respectively. Inhibition was weaker in NaCl (0.0003–0.0024 mm/y) and HCl (0.0037–0.0005 mm/y). Tafel polarization revealed a reduced corrosion rate in NaOH (0.00022 mm/y vs. 0.019 mm/y uninhibited) and a positive Ecorr shift. EIS demonstrated peak efficiency (75.5% at 0.8 mg/L in NaOH), supported by high charge transfer resistance Rct with about 6.80 × 104 Ω and oxide film resistance Rof with about 1.19 × 10⁶ Ω. SEM confirmed smoother surfaces in inhibited NaOH versus pitting in blanks. The extract’s efficacy in alkaline conditions rivals that of plant-derived inhibitors, though neutral/acidic performance was limited. These findings position S. crispus as a sustainable inhibitor for alkaline environments.